Economic development, alcohol consumption and life expectancy in low- and lower-middle-income countries in the Western Pacific Region: a structural equation modelling study - Jürgen Rehm; Huan Jiang; Ahmed S Hassan; Pol Rovira; Kevin D Shield (BMJ Public Health, 2025)
Introduction Economic transition has historically been shown to be associated with longer life expectancy in current high-income countries. We examined the role of alcohol consumption in this transition process for lower- and middle-income countries.Methods We tested three hypotheses on the interrelationship between economic growth, level of alcohol consumption and life expectancy in all six countries in the WHO Western Pacific Region, which transitioned from low- to lower-middle-income countries over the past 20 years. Structural equation modelling, corrected for autoregressive effects, was used to test the association between economic development and life expectancy, adult per capita consumption of alcohol, the prevalence of past-year drinkers and alcohol-attributable mortality. The direct impact of alcohol per capita consumption (APC) on life expectancy was also estimated.Results Overall, economic development was strongly positively associated with both life expectancy and alcohol consumption, and a higher level of alcohol consumption resulted in a lowered life expectancy, when directly measured. Thus, changes in gross domestic product per capita at purchasing power parity of $ 1000 Int. were linked to changes in the same direction in life expectancy of 0.94% (95% CI 0.66%, 1.21%) and with an increase in APC of 76.8% (55.38%, 98.3%). Average loss in life expectancy due to alcohol consumption was 1.76 (0.81, 2.72) years for males and 0.59 (0.12, 1.07) for females. There was heterogeneity found between countries.Conclusion Alcohol consumption is expected to increase in an economic transition from a low- to lower-middle-income country and to have a negative impact on life expectancy. Alcohol control policies should be enacted to reap the full health benefits of economic growth.